A 2001–2015 Archive of Fractional Cover of Photosynthetic and Non-Photosynthetic Vegetation for Beijing and Tianjin Sandstorm Source Region - Xiaosong Li; Zengyuan Li; Cuicui Ji; Hongyan Wang; Bin Sun; Bo Wu; Zhihai Gao (Data, 2017)
Fractional covers of photosynthetic and non-photosynthetic vegetation are key indicators for land degradation surveillance in the dryland of China. However, there are no available, well validated, and multispectral-based products. Aiming for this, we selected the Beijing and Tianjin Sandstorm Source Region as the study area, and utilized the linear spectral mixture model for generating the fractional cover of PV, NPV, and bare soil, with endmember spectra retrieved from the field measured endmember spectral library, based on the MODIS NBAR data from 2001 to 2015. The unmixing results were validated through comparison with the field samples. The results show the method adopted could acquire rational and accurate estimation of fractional cover of photosynthetic vegetation (R2 = 0.6297, RMSE = 0.2443) and non-photosynthetic vegetation (R2 = 0.3747, RMSE = 0.2568). The dataset could provide key data support for the users in land degradation surveillance fields.